2018
DOI: 10.4102/ajod.v7i0.419
|View full text |Cite
|
Sign up to set email alerts
|

Part 2: The feasibility of utilising photovoice method and the World Health Organization Quality of Life instrument in evaluating the Community-Based Rehabilitation programme in Namibia: A pilot study

Abstract: BackgroundEvaluation of Community-Based Rehabilitation (CBR) programmes in Namibia has been primarily quantitative, focusing mainly on outputs, including numbers of persons with disabilities served, referrals made and activities implemented. Little or no evidence is available on experiences and quality of life of persons with disabilities, despite the CBR programme being operational for more than 20 years. The 2011 World Report on Disability recommended the use of appropriate tools to fill the research gap by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…They found that photovoice provided the opportunity for elderly African Americans to share their beliefs and perspectives with regard to self-care, and this easy-to-use intervention eventually empowered vulnerable participants [9]. Another study had also tried this new approach and considered photovoice as an intervention, measuring the outcome (that is, quality of life) after the participants went through the photovoice process [24]. The finding of the current study provided additional evidence that photovoice can be extended from a research methodology to an intervention, and that this was an appropriate intervention for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…They found that photovoice provided the opportunity for elderly African Americans to share their beliefs and perspectives with regard to self-care, and this easy-to-use intervention eventually empowered vulnerable participants [9]. Another study had also tried this new approach and considered photovoice as an intervention, measuring the outcome (that is, quality of life) after the participants went through the photovoice process [24]. The finding of the current study provided additional evidence that photovoice can be extended from a research methodology to an intervention, and that this was an appropriate intervention for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through adapting the photovoice methodology in line with any disability or CBR framework, for example using the WHO CBR Matrix in data analysis. Further, Shumba and Moodley [28] as part of their study, developed posters for public photo exhibitions to share photographs and findings with the broader community and policymakers to advocate for development and changes to disability policy, legislation and programs. Utilizing photovoice as a research method will enhance the understanding of people with disabilities, enabling them to better articulate their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a combination of photovoice and WHOQOL-BREF and WHOQOL-Dis assessment has the potential to give an adequate representation of the voices of persons with disabilities and their quality of life. Further, Shumba and Moodley [28], concluded that the WHOQOL-BREF and WHOQOL-Dis can be administered at the end of the photovoice process to depict the convergence and divergence of both the experiences of persons with disabilities and their quality of life regarding CBR.…”
Section: Overview Of Cbr Evaluationmentioning
confidence: 99%
“…Vol. 32, No.2, 2021; doi 10.47985/dcidj.408 Photovoice Method -Data was collected and analysed utilising the modifi ed Photovoice method by Shumba and Moodley (2018c) which is illustrated in Figure 1. All individual interviews were transcribed verbatim, and the constant comparative approach (Patt on, 2002) was utilised during the data analysis.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Shumba and Moodley (2018b) also confirmed the need to explore the experiences of persons with disabilities in CBR programmes using appropriate qualitative evaluation tools. A scoping review established that Photovoice has the potential to be utilised as a qualitative evaluation tool for effectively eliciting the experiences of persons with disabilities on a CBR programme (Shumba & Moodley, 2018c).…”
Section: Introductionmentioning
confidence: 99%